2024
DOI: 10.1590/1806-9282.20230264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-level laser therapy on acupuncture points on knee pain and function in knee osteoarthritis

Ayşegül Yetişir,
Gülşah Yaşa Öztürk

Abstract: OBJECTIVE: Knee osteoarthritis is a common and disabling disease. We aimed to examine the effect of low-level laser therapy in addition to routine physical therapy modalities (transcutaneous electrical stimulation, superficial heating modality of infrared, ultrasound, and exercise) on the functional status and pain in knee osteoarthritis. METHODS: Patients with knee osteoarthritis (n=71) who underwent physical therapy (transcutaneous electrical stimulation, infrared, ultrasound, exercise therapy, and low-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…It relieves pain, adjusts nerve function, and promotes circulation. An investigation study showed that electroacupuncture was used to treat patients with otogenic vertigo for four weeks, and after treatment, the hearing of both patients returned to a normal threshold and no adverse events occurred[ 29 ]. Reported that electroacupuncture at the Fengchi Fuxue point relieved the patient’s vertigo, with a clinical effect of improved blood flow in cerebral arteries and the degree of cerebral artery atherosclerosis, and reduced blood viscosity[ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…It relieves pain, adjusts nerve function, and promotes circulation. An investigation study showed that electroacupuncture was used to treat patients with otogenic vertigo for four weeks, and after treatment, the hearing of both patients returned to a normal threshold and no adverse events occurred[ 29 ]. Reported that electroacupuncture at the Fengchi Fuxue point relieved the patient’s vertigo, with a clinical effect of improved blood flow in cerebral arteries and the degree of cerebral artery atherosclerosis, and reduced blood viscosity[ 30 ].…”
Section: Resultsmentioning
confidence: 99%